How well is paediatric pain managed in a private hospital in London? An evaluation of paediatric healthcare providers' pain management practices and parents' perception of pain management in their hospitalized children - Oladoyinbo, Abidemi (Department of Public Health and Family Medicine, 2019)
Background: Optimal pain relief in a healthcare setting relies heavily on actual pain management practices rather than just on the healthcare practitioner’s knowledge of this. Understanding parents' perceptions of pain management practices are very important in identifying areas of concerns and in developing plans and strategies for improvement. Although research has examined these practices in various public healthcare settings, no research has been carried out within the private sector. Aims/Objectives: This study aims to evaluate pain management practices of paediatric healthcare providers and parental perception of these practices within a private hospital in London. Its main objectives to evaluate paediatrics health care providers’ pain management practices against the recommended standard within the UK. Methods: Using a Mixed method study design, 10 healthcare providers were observed and data was collected on pain management of 10 children over a period of 10 months (14 shifts). Interviews were also conducted with the corresponding 10 parents/caregivers of children involved in the study. Results: The median age of child participant and health care providers were 3 and 32years respectively. Greater than half of the parent participants were Arabic while there was a fairly equal representation of white, Asian and black racial distribution among the health care providers. Although all healthcare provider could speak English, almost half of them could speak other languages, while greater than half of parent participant speaks Arabic. Pain assessment is routinely documented when the vital signs are checked, but recorded score may not correlate with the actual pain score of the child. This is due to lack of consistency and appropriate use of a validated pain tool for age. A potential lack of knowledge on how to utilise the various assessment tools may also contribute. Most parents were satisfied with the pain management of their child. They did indicate, however, the need to improve healthcare providers’ competencies and knowledge in the use of pain relieving devices as well as in the provision of supportive information for parents. Conclusion: Overall, pain management practices in Harley Street were found to be satisfactory. Parental satisfaction with care provided could be attributed to the team approach utilised by healthcare providers in pain management. It is recommended that Harley Street Clinic needs to implement a paediatric specific pain management guidelines with regular auditing of pain management practices in the hospital. A review of pain management information given to parents of cardiac patients, as well as the provision of pain management information brochure in relevant languages may help improve care.